The EU-Japan Economic Partnership Agreement: Relevance, Content and Policy Implications - Michael Frenkel; Benedikt Walter (Intereconomics, 2017)
On 6 July 2017, after four years of negotiation, the EU reached an agreement with Japan over the main elements of a comprehensive free trade agreement. The breakthrough came at a time when progress on multilateral trade negotiations at the global level seemed out of reach and EU bilateral trade agreements faced strong public opposition. This paper examines the content of the new agreement with a view to global trade dynamics and assesses its main trade policy implications.
Keywords: 330